ANALISIS UPAYA PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN IPA - Krisna Saputra; Luthfia Azizah; Nurma Meinda Ira Saputri; Nyoto Suseno (JURNAL FIRNAS, 2024)
Abstract: Education in the 21st century era is characterized by advances intechnology and information, the independent curriculum is the focus fordeveloping students' character and basic competencies. However, the low levelof creativity of Indonesian children, especially in the context of science, is a majorconcern. This low level of creative thinking can have a negative impact onstudents' learning achievement, so this research is important in identifying andovercoming these challenges. This research aims to find the best solution toimprove the creative thinking skills of seventh grade students at SMPN 9 Metro.The research method used is descriptive qualitative with a triangulationapproach, combining observation, interviews, and literature study. Learning thatstill relies on the lecture method is considered less effective for training creativethinking skills. The results showed that creative thinking skills can be effectivelyreviewed using the Creative Problem Solving (CPS) model. CPS is a structuredprocess that emphasizes divergent and convergent thinking to produceinnovative solutions to problems. Several studies support the effectiveness ofCPS in improving students' creative thinking skills. The results of the analysisconcluded that students' creative thinking skills can be improved through theapplication of the CPS model which shows the positive impact of using CPS inscience learning.